2012
DOI: 10.1007/s00402-012-1510-y
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment and prognosis in patients with high-grade soft tissue malignant fibrous histiocytoma of the extremities

Abstract: The overall prognosis is poor. LR, although can be managed with tumor re-excision, has high second recurrence rate. Increased tumor size is associated with shorter metastasis-free interval which significantly decreases survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…[12] Postoperative radiation therapy has been recommended for patients with marginal surgical margins in postoperative histological evaluation. [13,15,16] In our series, radiotherapy was administered to three patients with marginal surgical margins. Reports of the outcome of the patients who received loco-regional treatment as surgery alone and/or radiation therapy were disappointing, and adjuvant chemotherapy was introduced with encouraging results.…”
Section: Discussionmentioning
confidence: 99%
“…[12] Postoperative radiation therapy has been recommended for patients with marginal surgical margins in postoperative histological evaluation. [13,15,16] In our series, radiotherapy was administered to three patients with marginal surgical margins. Reports of the outcome of the patients who received loco-regional treatment as surgery alone and/or radiation therapy were disappointing, and adjuvant chemotherapy was introduced with encouraging results.…”
Section: Discussionmentioning
confidence: 99%
“…Although great advances have been achieved in the treatment, oncological outcome in spinal sarcomas is worse than that of soft tissue sarcomas in extremities20,33,40). In extremity sarcomas, many reports on survival and recurrence are available2,31,36,37). Vasileios et al37) reported that 5-year survival rate of MFH patients was 66% and the recurrence and the metastasis rates were 31%.…”
Section: Discussionmentioning
confidence: 99%
“…In extremity sarcomas, many reports on survival and recurrence are available2,31,36,37). Vasileios et al37) reported that 5-year survival rate of MFH patients was 66% and the recurrence and the metastasis rates were 31%. Tural et al36) reported that the recurrence rate was 23% and 5-year survival rate was 72% through retrospective study of adult Ewing sarcoma patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Nevertheless, the Association of Directors of Anatomical and Surgical Pathology recommends that any margin macroscopically more than 5 cm is believed to be clear. 31,32 In our patients, the lesion was removed as widely or radically as possible.…”
Section: Discussionmentioning
confidence: 99%